DAYA DUKUNG LAHAN PERTANIAN TANAMAN PANGAN DI KABUPATEN MINAHASA SELATAN - Andre Giant Galentsi Masengi; Celcius ., Talumingan; Juliana R. Mandei (Sam Ratulangi University, 2015)
This research aims to determine the carryng capacity of agricultural land food crops in Southern Districts Minahasa. This research from preparation of the final report of the study conducted in March to June 2015. Data is taken from secondary data obtained from the Central Statistical Agencies and the Department of Agriculture in Southern Minahasa. The data analysis used is the level of the carryng capacity of agricultural land. From the research the level of the carrying capacity of agricultural land, the lowest in the sub-district of ModoindingÂ was in the amount of 0,076 and the highest in the sub-district of Maesaan that is equal to 1,113. Carrying value of the level of agricultural land in the Southern District Minahasa amounted to 0,414. This means that the Southern Minahasa District has not been able to perform self-suffieciency and has not been able to provide a decent life for its people, therefore the carrying capacity of agricultural land food crops in Southern Minahasa district needs to be improved especially through increased productivity and reduce the rate of population growth.